2014
DOI: 10.1088/0957-4484/25/22/225603
|View full text |Cite
|
Sign up to set email alerts
|

Single step synthesis and organization of gold colloids assisted by copolymer templates

Abstract: We report here an original single-step process for the synthesis and self-organization of gold colloids by simply incorporating gold salts into a solution prepared using polystyrene (PS)-polymethylmethacrylate copolymer and thiolated PS with propylene glycol methyl ether acetate as a solvent. The spin-coating and annealing of this solution then allows the formation of PS domains. Depending on the polymer concentration of the as-prepared solution, there can be either one or several gold nanoparticles (Au NPs) p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…Simulation results of circuit shown in (d) shows the appearance of a second peak whose behavior is a mirror of the first. (e) The results of DDA calculations of collodial Au-Au in organic liquid shows the trend in peak position with proximity effect [46] and our simulation (f ) matches quite well with results.…”
Section: Nano-particles In Proximity Embedded In Dielectricsupporting
confidence: 84%
See 3 more Smart Citations
“…Simulation results of circuit shown in (d) shows the appearance of a second peak whose behavior is a mirror of the first. (e) The results of DDA calculations of collodial Au-Au in organic liquid shows the trend in peak position with proximity effect [46] and our simulation (f ) matches quite well with results.…”
Section: Nano-particles In Proximity Embedded In Dielectricsupporting
confidence: 84%
“…as the inter-particle distance decreases, the peak shifts towards lower wavelengths. In other words, this new peak shows a blue-shift with increasing proximity [see fig4(d)].Experimentally, this second peak is usually a "minor" (in terms of absorption intensity) peak[46], [fig 4(e)]. Our simulations [fig 4(f)] replicated the results of fig 4(d), i.e.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…The working principle of the first prototype, developed by Liz-Marzan and co-workers, was based on a drop of the light absorption when the substrate is stretched, and less NPs are illuminated . Very quickly, other groups (including ours) investigated color-changing stretchable films exploiting the variation of the plasmonic coupling between NPs when strains, applied to the substrates, lead to NP displacements. Finally, by embedding free-standing nanorod arrays into an elastomeric thin film, it has been demonstrated that suitable excitation conditions (off-normal incidence) can induce both long and short axis plasmon oscillations and can also be exploited for strain sensing applications . These pioneering works lead to the emergence of a new field, which can be identified as “plasmomechanics,” and whose essence is based on both the use of mechanical stress to investigate plasmonic coupling and on plasmonic coupling monitoring to detect strains applied to the substrate …”
Section: Introductionmentioning
confidence: 99%